Cutis vertices gyrate: a case report - Narang, Gursharn Singh; Jasleen, Jasleen; Kaur, Jaskeen; Kaur, Tanreet (International Journal of Contemporary Pediatrics, 2018)
Cutis verticis gyrata is a rare condition characterized by excessive growth of skin of the scalp, resulting in furrows and folds similar to gyri of the cortex of brain. It can be classified into two forms: primary (essential and non-essential) and secondary. We report a case of 18-year-old male patient with primary essential cutis verticis gyrata with rugosities over forehead and scalp and coarse facial features.